Vasoconstrictor effect of Africanized honeybee (Apis mellifera L.) venom on rat aorta - Paulo César P Sousa (Journal of Venomous Animals and Toxins including Tropical Diseases, 2013)
Background : Apis mellifera stings are a problem for public health worldwide, particularly in Latin America due to the aggressiveness of its Africanized honeybees. Massive poisoning by A. mellifera venom (AmV) affects mainly the cardiovascular system, and several works have described its actions on heart muscle. Nevertheless, no work on the pharmacological action mechanisms of the AmV in isolated aorta has been reported. Thus, the present work aimed to investigate the actions of AmV and its main fractions, phospholipase A2 (PLA2) and melittin, on isolated aorta rings and a probable action mechanism. Results : AmV and the complex PLA2 + melittin (0.1-50 μg/mL) caused contraction in endothelium-containing aorta rings, but neither isolated PLA2 nor melittin were able to reproduce the effect. Endothelium removal did not change the maximum vasoconstrictor effect elicited by AmV. Ca2+-free medium, as well as treatment with phentolamine (5 μM), verapamil (10 μM), losartan (100 μM), and U-73122 (10 μM, a phospholipase C inhibitor), eliminated the AmV-induced contractile effects. Conclusions : In conclusion, AmV caused contractile effect in aorta rings probably through the involvement of voltage-operated calcium channels, AT1 and α-adrenergic receptors via the downstream activation of phospholipase C. The protein complex, PLA2 + melittin, was also able to induce vasoconstriction, whereas the isolated proteins were not.